Quantitative MS analysis of therapeutic mAbs and their glycosylation for pharmacokinetics study. Issue 4 (10th December 2015) - Cong, Yuting; Zhang, Zhang; Zhang, Shen; Hu, Lianghai; Gu, Jingkai
Abstract : Therapeutic mAbs play an important role in the treatment of a wide range of diseases. Due to their complexity, comprehensive evaluation of their pharmacokinetics has yet to be fully achieved. It is crucial to develop sensitive, accurate, reliable, and reproducible methods for quantitation of mAbs in complex samples. In addition, it is also important to evaluate the PTMs which can affect their safety and/or effectiveness. MS‐based methods provide an emerging approach for quantitation of proteins and their modification forms. In this review, we give a brief overview of quantification analysis of mAbs in complex biological samples and the characterization of N‐glycosylation by biological MS.